THE INFLUENCE OF NON-GOVERNMENT EXPERT AND ANALYTICAL CENTERS ON THE PROCESS OF POLITICAL DECISION-MAKING IN UKRAINE - Рубанов, В.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The essential features and forms of activities of non-governmental expert and analytical frames as subjects of political decision-making are examined. It is demonstrated the specific of main problems of its forming and development of Ukrainian society. Proposes recommendations about perspectives to attach to independent expert and analytical centers and agencies to the process of preparation, decision-making and realization of political resolutions and programs in Ukraine.